Demographic and Clinical Pattern of Headache in Migraine Patients (Bangladesh Journal of Neuroscience, 2019)
Background: Migraine is one of the most common neurological disorder and fourth most important factor for debility in human. The presentation of migraine is complex. All patients do not have same features of migraine.Objectives: The purpose of the study was to evaluate demographic and clinical patterns of headache in migraine patients.Methods: A total of 30 migraine patients who were visited in the Headache clinic, Department of Neurology, BSMMU, Dhaka were enrolled for the study. Migraine patients diagnosed according to ICHD-3 (International Classification of Headache Disorders 3rd edition) criteria.Results: Out of 30 patients mean age was 30.63±10.95 years with age range 15-60 years in migraine patients. Female were more common. Positive family history was present in 56.7% patients. Common associated symptoms were photophobia, phonophobia (96.7%) and nausea (83.3%) in migraine patients. Common precipitating factors were stress and sunlight (90%) followed by journey (80%) and insomnia (73.3%). A major portion of migraine was without aura (73.3%) and the ratio of aura to without aura is 1: 2.75. Major portion of migraine patients were complained of 4-6 attacks/ month (46.7%) which was followed by 1-3 attacks/month (36.7%). Most of the migraine patients complained as moderate headache (60%) followed by severe headache (40%).Conclusion: This study concluded that migraine is a disease of younger age group and it affects female more commonly than male, pattern of headache in migraine patients is unique.Bangladesh Journal of Neuroscience 2019; Vol. 35 (2): 63-68